Cambodian diary tales of a divided nation 1983-1986 - Bekaert, Jacques (White Lotus Press, 1997)
T he diaries cover the turbulent and dramatic recent history of Cambodia (1983-1986). We see a country emerging from the disaster of the Khmer Rouge era, only to find itself embroiled in a protracted war. This first volume discusses the ups and downs of the resistance, the secretive life of the communist party, the suffering of the people, the emergence of new leaders, like Prince Ranariddh and Hun Sen, and the continuous efforts of Prince Sihanouk to bring peace to his troubled land. The diary moves, week after week, from the Thai-Cambodian border to Hanoi, Beijing, Bangkok, Paris or Washington and of course to Phnom Penh and the Cambodian countryside. From the Khmer Rouge to born-again capitalists, from low intensity conflict to international intrigues, here is a first hand history of contemporary Cambodia.